Annual Plan 2001-2002 Volume III Scheme Wise Plan Outlay Government of National Capital Territory of Delhi - Planning Commission (Planning Commission, 2001)
Sector/Department/Agency wise Outlay and Expenditure, Sector/Scheme wise Outlay and Expd., Agriculture and Allied Services, Co-operation, Rural Development, Minor Irrigation, Flood control, Energy, Industries Weight and Measures, Transport, Science Tech. and Environment, General Eco. Services, Tourism, Survey and Statistics, Civil Supplies, General Education, Technical Education, Centrally Sponsored Schemes 2001-2002.
Government of National Capital Territory of Delhi, Planning Department